A Means to Many Ends: Promoting Faculty Diversity in Christian Higher Education through the Institutionalization of Service-Learning. Issue 5 (20th October 2021) - Lewing, James Morgan
Abstract: The demographics of higher education, including Christian higher education, are changing as campuses are experiencing an increase in enrollment of African, Latino(a), Asian, and Native American (ALANA) students. Increasing faculty diversity, however, has not kept pace with increasing student diversity. In addition to supporting a rapidly changing student body, institutional identification of strategies to develop, recruit, support, and retain ALANA faculty members is needed. Diversification efforts are most successful when a supportive organizational ethos and an inclusive academic environment are established that promote and value the unique contributions of a diverse group of faculty members. Drawing upon research that has focused on service-learning, faculty motivation, and theoretical frameworks in the fields of student development, organizational psychology, and marketing, this article suggests that the institutionalization of service-learning can serve as a strategic mechanism for supporting faculty diversification in Christian higher education.